The Creation of a Pediatric Health Care Learning Network: The ACTION Quality Improvement Collaborative. Issue 4 (April 2020) - Lorts, Angela; Smyth, Lauren; Gajarski, Robert J.; VanderPluym, Christina J.; Mehegan, Mary; Villa, Chet R.; Murray, Jenna M.; Niebler, Robert A.; Almond, Christopher S.; Thrush, Philip; O'Connor, Matthew J.; Conway, Jennifer; et al.
Abstract : Improving the outcomes of pediatric patients with congenital heart disease with end-stage heart failure depends on the collaboration of all stakeholders; this includes providers, patients and families, and industry representatives. Because of the rarity of this condition and the heterogeneity of heart failure etiologies that occur at pediatric centers, learnings must be shared between institutions and all disciplines to move the field forward. To foster collaboration, excel discovery, and bring data to the bedside, a new, collaborative quality improvement science network—ACTION (Advanced Cardiac Therapies Improving Outcomes Network)—was developed to meet the needs of the field. Existing gaps in care and the methods of improvement that will be used are described, along with the mission and vision, utility of real-world data for regulatory purposes, and the organizational structure of ACTION is described.